Evaluation of Surface Microhardness of Silver and Zirconia Reinforced Glass-ionomers with and without Microhydroxyapatite - Sharafeddin F; Azar MR; Feizi N; Salehi R (Shiraz University of Medical Sciences, 2017)
Statement of problem: Hardness of restorative materials like glass-ionomer is an important factor in the longevity of restoration. Objectives: The aim of this study was to evaluate the microhardness of glass-ionomer modified with different materials. Materials and Methods: Sixty disk-shaped specimens were examined in six groups in this study, including conventional glass-ionomer (Shofu, Japan), zirconia-reinforced glass-ionomer (Zirconomer, Shofu, Kyoto, Japan), silver-reinforced glass-ionomer (HI-DENSE XP, Shofu, Kyoto, Japan) and mixture of these three types of glass-ionomer with 20 wt% of microhydroxyapatite (Sigma-Aldrich, St. Louis, USA). All the specimens were stored in deionized water for 24 hours. Then Vickers microhardness test was carried out and the results were analyzed by using two-way ANOVA test and paired t-test (P<0.05). Results: Zirconia-reinforced glass-ionomer with microhydroxyapatite exhibited significantly higher microhardness in comparison with other groups (P<0.001). Conventional glass-ionomer with microhydroxyapatite showed the lowest microhardness (P<0.001). After incorporation of microhydroxyapatite in both conventional and silver-reinforced glass-ionomer groups, microhardness decreased significantly (P<0.001).The microhardness of top and bottom of all groups was significantly different. (P<0.001). Conclusions: Incorporation of 20% microhydroxyapatite to zirconia-reinforced glass-ionomer can improve microhardness.